Practice of Determining Notary Honorarium Related to Authentic Deed Preparation Services - Saleh, Moh.; Darmawan, Aldio (Jurnal Hukum dan Keadilan, 2025)
A notary is a public official authorized to create authentic deeds and exercise other authorities as outlined in the UUJN and other relevant laws. While the primary function of a notary is to draft authentic deeds, their authority extends beyond this role. This study aims to analyze how the UUJN regulates the honorarium for a notary’s services beyond the creation of authentic deeds. The research adopts a normative juridical approach, focusing on legal principles and statutory regulations. It highlights that the minimum notary fee is not explicitly defined in the UUJN or other related laws. Although there are provisions regarding notary fees for drafting authentic deeds, there is a lack of clarity on fees for other notarial services. This ambiguity can lead to varied interpretations and practices in determining notarial fees, potentially affecting the standardization of notarial services. Given the importance of a notary’s role in legal transactions, clearer regulations regarding fees for non-authentic deed-related services are necessary. Establishing a well-defined framework would enhance transparency, ensure fairness, and maintain professional standards. Therefore, further legal evaluation and potential amendments to the UUJN may be needed to address this issue effectively